2021
DOI: 10.1016/j.clineuro.2021.106654
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the COVID-19 pandemic on patients with chronic inflammatory demyelinating polyradiculoneuropathy

Abstract: Objectives At a time of global health crisis, fear, anxiety, and stress levels increase. The effects of protracted social isolation, and media related misinformation’s about the coronavirus disease 2019 (COVID-19) resulting in increased fear/stress related to the insufficiently known illness. The aim was to assess the influence of the COVID-19 health crisis on patients with chronic inflammatory demyelinating polyradiculoneuropathy (CIDP). Methods A cross-sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…But contacts were also reduced on the patient side. People went to the hospital less often out of fear for potential infection [16][17][18]. This is also shown in the study of Musche et al Despite evidence of reduced infections from immunotherapy in patients with CIDP and MMN, the prevalence of depression and fear of potential infection has increased [19].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…But contacts were also reduced on the patient side. People went to the hospital less often out of fear for potential infection [16][17][18]. This is also shown in the study of Musche et al Despite evidence of reduced infections from immunotherapy in patients with CIDP and MMN, the prevalence of depression and fear of potential infection has increased [19].…”
Section: Discussionmentioning
confidence: 78%
“…Partially due to the global shortage of intravenous immunoglobulins, 27.4% (2021) of our patients required adjustments in therapy (38.4% in 2022) [9,10,18]. Despite the fact that the study of Romozzi et al [21] indicates that patients were also able to cope with less or no immunoglobulins due to the pandemic, 50.0% (2021) of our cohort reported worsening of symptoms (67.9% in 2022).…”
Section: Global Shortage Of Intravenous Immunoglobulinsmentioning
confidence: 86%
“…To the best of our knowledge, we were the first to conduct a study of patients with CIDP or MMN in direct comparison to healthy controls during the pandemic. Stojanov et al [ 13 ] reported not only a direct effect of COVID-19 but also an indirect effect on patients with CIDP; 62% of the patients reported concerns, 55% a reduction of daily activities, and 39% an influence on their CIDP therapy. These concerns and changes in daily life and treatment could explain why the present sample showed increased COVID-19-related fear, depressive symptoms, and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, cohort studies showed that the course of disease and outcomes for patients with neuroimmunological diseases seem to be ambiguous [ 8 , 9 ]. While, for instance, Salter et al [ 10 ] showed that the risk of severe outcomes from COVID-19 in individuals with CIDP was similar to that seen from the general population, other studies revealed that individuals with CIDP are at greater risk of COVID-19 infection, but also disease exacerbations and relapses due to infection with SARS-CoV-2 [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the future, multicenter studies or more interview scenarios should be considered, such as homes and communities. Finally, although COVID-19 has negatively impacted many people's lifestyles, mental health, and quality of life (Stojanov et al, 2021;Motolese et al, 2020) and recently exacerbate social isolation, this special medical social background was not taken into account in the interviews. However, the epidemic situation in China was in a relatively stable period from November 2020 to March 2021.…”
Section: Discussionmentioning
confidence: 99%